Effects of intraoperative pyloric stretch procedure on outcomes after esophagectomy. Issue Volume 31:Issue10(2018) (29th May 2018) - Boshier, P R; Adam, M E; Doran, S; Muthuswamy, K; Hanna, G B
Summary: Various methods have been described to aid pyloric drainage in patients undergoing esophagectomy with gastric reconstruction. These techniques are intended to prevent delayed gastric empting following esophagectomy that can be associated with early morbidity and long-term functional complaints. The current study aims to review the safety and efficacy of a pyloric stretch procedure performed at the time of esophagectomy. To achieve this, a retrospective review of 100 consecutive patients undergoing esophagectomy during the period 2011–2016 was performed. Until May 2013, no patients received intraoperative pyloric intervention. After May 2013, all patients ( N  = 50) underwent intraoperative pyloric stretch procedure that involved bidirectional mechanical dilatation of the pylorus. Postoperative outcomes including result of routine oral contrast swallow and early morbidity were evaluated. Intraoperative pyloric stretching was performed safely and without local complications in all patients. Delayed gastric emptying was observed significantly less frequently in patients who received intraoperative pyloric stretching (48% vs. 22%, P  = 0.006). No significant differences were observed in postoperative outcomes. When considering all patients as a single cohort, the presence of delayed gastric emptying was associated with significantly higher rates of postoperative pneumonia (71% vs. 45%, P  = 0.010), cardiac complications (57% vs. 25%, P  = 0.001) as well as longer hospital say (12 vs. 15 days, P  < 0.001) and delay to free oral fluid intake (7 vs. 9 days,  < 0.001). Binary logistic regression identified age and postoperative delayed gastric emptying as independent risk factors for postoperative pneumonia. In conclusion, this study has demonstrated the safety and efficacy an intraoperative pyloric stretch procedure for the prevention of delayed gastric emptying following esophagectomy.